Winter forage selection by barren-ground caribou: Effects of fire and snow - Saperstein, Lisa (Rangifer, 1996)
Both long- and short-term consequences should be considered when examining the effects of fire on the foraging behavior of caribou. Post-fire increases in protein content, digestibility, and availability of E. vaginatum make burned tussock tundra an attractive feeding area for caribou in late winter. These benefits are likely short-lived, however. Lowered availability of lichens and increased relative frequency of bryophytes will persist for a much longer period.